-5+8x=-8x+23

Simple and best practice solution for -5+8x=-8x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5+8x=-8x+23 equation:


Simplifying
-5 + 8x = -8x + 23

Reorder the terms:
-5 + 8x = 23 + -8x

Solving
-5 + 8x = 23 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-5 + 8x + 8x = 23 + -8x + 8x

Combine like terms: 8x + 8x = 16x
-5 + 16x = 23 + -8x + 8x

Combine like terms: -8x + 8x = 0
-5 + 16x = 23 + 0
-5 + 16x = 23

Add '5' to each side of the equation.
-5 + 5 + 16x = 23 + 5

Combine like terms: -5 + 5 = 0
0 + 16x = 23 + 5
16x = 23 + 5

Combine like terms: 23 + 5 = 28
16x = 28

Divide each side by '16'.
x = 1.75

Simplifying
x = 1.75

See similar equations:

| 34x*2= | | x/7-23=48 | | 2(11+8n)=-26+12n | | a^2-10a+n=0 | | x+0.070=0.350 | | 2w(5w+3)=0 | | 2(x+2)3x=2(x+1)+1 | | 2[2(3-5x)+4]=5[2(3-3)+2] | | 30-5(6x+5)= | | 1-6x=6-x | | -4(2x+11)=11 | | 2x+45=x-5 | | x^3+7x^2-9x=63 | | x^2+27x+6=0 | | y^2+18y+13=-4 | | -2(y+3)=2y+3 | | x/2+16=77 | | 2(4+4r)+3r=63 | | y^3-7y^2+10=0 | | c/2+16=77 | | 3d-24-5=9b+18+1 | | 2(4+4r)+3=63 | | 7n^2-14n+54=-5 | | 13+17y-3(y+11)= | | 5n+3=9 | | -7=-11+x/5 | | -t+2=10 | | 6y-9y=-16-20 | | 5b^2=-12 | | 55-40=30 | | -8x-2-9x-1=4 | | 14x+13-8x-1= |

Equations solver categories